PENGEMBANGAN MEDIA SCRAFBOOK TERHADAP HASIL BELAJAR SISWA KELAS 1 SEKOLAH DASAR - Alvionita Sari, Vivi; Satrio Wibowo; Galuh Kartika Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The background of this researcher was to develop a scrafbook learning media to improve the learning outcomes of grade 1 students at SDN 3 Pucanga Sidoarjo on theme 1 "Myself" sub-theme 2 "My Body". The aim of this research is to find out whether the ScrafBook media is suitable for use with 1st grade elementary school students and to find out the learning outcomes of 1st grade elementary school students after using ScrafBook media. This research uses the development or R&D method with the ADDIE model which uses 5 procedures, namely analyze, design, development, implementation, and evaluation. This research was conducted at SDN 3 Pucang Sidoarjo which consisted of 23 samples. The media validation results resulted in 82% being categorized as suitable for use and the material validation results being 98% or categorized as suitable for use. From the test results, students in class 1 of SDN 3 Pucang Sidoarjo produced effective learning results, namely 64.30 in the pretest and 79.56 in the posttest with an N-Gain value of 64.14. The results of this research are very suitable for use and improve the learning outcomes of class 1 students at DN 3 Pucang Sidoarjo.